What are the most important characteristics of effective Continuous Professional Learning (CPL) within an urban secondary school? - Fuller, Amy (2017)
“all natural learning experiences and those conscious and planned activities which are intended to be of direct or indirect benefit to the individual, group or school and which contribute, through these, to the quality of education in the classroom”. Day (1999: 18)